2019
DOI: 10.1108/jiabr-05-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Financial sustainability of statewaqfinstitutions (SWIs) in Malaysia

Abstract: Purpose-This paper aims to measure the financial sustainability and vulnerability of state-managed waqf institutions in Malaysia. Design/methodology/approach-The study mainly applied the commonly used Tuckman and Chang's (1991) model to measure the financial health of non-profits. Content and ratio analysis of the 2014 audited reports of seven institutions were used to determine their equity balance, revenue concentration, administrative costs and operating margin ratios. Findings-The results indicate that onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 38 publications
1
39
0
3
Order By: Relevance
“…Initial investigations found that there are many problems in waqf financial statement, such as no standardisation and not updated. This supports previous literature, where it was found that Islamic councils practiced different reporting (Sulaiman et al, 2019;Daud et al, 2011;Yunanda et al, 2016;Masruki and Shafi, 2013;Mohamed et al, 2006). This might be due to the lack of mandatory regulation.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Initial investigations found that there are many problems in waqf financial statement, such as no standardisation and not updated. This supports previous literature, where it was found that Islamic councils practiced different reporting (Sulaiman et al, 2019;Daud et al, 2011;Yunanda et al, 2016;Masruki and Shafi, 2013;Mohamed et al, 2006). This might be due to the lack of mandatory regulation.…”
Section: Introductionsupporting
confidence: 89%
“…Unfortunatley, this is not the case in the present situation for waqf. It was found that there is a lack of reporting on waqf matters (Sulaiman, et al, 2019;Daud and Rahman, 2018;Yunanda et al, 2016;Masruki and Shafi, 2013;Mohamed, Daud, Md. Zain and Yaccob, 2006;Daftardar, 2008;Daud, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) Adeyemi et al. (2016) Sulaiman and Zakari (2019) Pitchay et al. (2018) Thaker (2018) Thaker et al.…”
Section: Existing Researchmentioning
confidence: 99%
“…Three indicators were used to determine financial performance, namely: (i) net income ratio (NIR); (ii) operating income ratio (OIR); and (iii) income growth (IG). Meanwhile, another four indicators were used to indicate financial sustainability, which are: (i) equity balances (EB); (ii) administrative costs ratio (ACR); (iii) revenue concentration index (RCI); and (iv) operating margin ratio (OMR) (Shafii et al, 2014;Sulaiman & Zakari, 2019). The use of audited financial information to determine both financial performance and sustainability is considered reliable due to the importance of the information published and those information have been verified before arriving at a conclusion by the auditor (Froelich et al, 2000).…”
Section: E T H O D O L O G Ymentioning
confidence: 99%